The courage to lead through values : how management by values supports transformational leadership, culture, and success - Norlin, Liza-Maria (Productivity Press, 2020)
As society rapidly increases in complexity, we are in great need of sustainable leadership in accord with beliefs and values as we experience continuous changes. The Courage to Lead through Values: How Management by Values Supports Transformational Leadership, Culture, and Success is about having the courage to lead through the implementation of agreed-upon values. In addition, it's about the courage it takes to never cease doing this. However, it's not enough to simply be aware of the importance of constantly working with values and ethics -- effective leadership based on values and ethics means taking the time to actually do it. This book tackles this issue by providing you with clear examples of how to implement incorporating values and ethics in your everyday leadership. In business, you face challenges when you must choose between efficiency, analysis of results, and goals versus actively working on values and ethics. This book will argue that one doesn't need to compete with the other and it posits that one supports the other. As the world is rapidly growing in complexity and we are facing new challenges and expectations, we must find ways to achieve sustainable lives, businesses, and societies. The author strongly believes that values are the key. By using the methodology Management by Values (MBV), under the mentorship of its founder, Professor Simon L. Dolan, the book is well-anchored in research. Ten years ago, a new school was founded in a medium-sized town in Sweden -- Internationella Engelska Skolan Sundsvall. It started with a staff of 20 and 250 students. Today the staff has grown to 120 members with nearly 1100 students attending. In 2019, it was considered one of the best schools in Sweden. The principal, Pascal Brisson, in many ways epitomizes the school and its success. Through in-depth interviews with the principal and colleagues, previous staff, executives within the organization and students, the author amassed information to provide a factual and engaging story of the school's journey from a leadership perspective. It becomes clear how implementing shared values and the principal's courage to never stop actively working with values as a management tool is a recipe for the success of an organization. The book invites you into a conversation about leadership. It includes the author's personal reflections on historical management methodology and on challenges of today. As you follow the ten-year journey of a successful leader in one of our society's most complex organizations, a school, you do this in the light of Management by Values. Essentially, this book gives the reader concrete tools and examples of how to use values as a management tool. This is told through several different themes relevant to all organizations -- organizational culture, creating teams, inspiring motivation, and handling stress.